Optimalisasi Pembuatan Website Personal bagi Pengajar di Lembaga Pengembangan Dakwah Al-Bahjah Cirebon - Putra, Bayu Wijaya; Afif, Hasnan; Ruskan, Endang Lestari; Kurniawan, Dedy; Ibrahim, Ali; Kurniawati, Junia; Efendi, Rusdi; Apriansyah, Apriansyah; Sari, Purwita; Marjusalinah, Anna D.; Sazaki, Yoppy (ASOSIASI IDEBAHASA KEPRI, 2025)
Website development usually involves programming experts in creating websites as information media and a server is needed as a home for the website being developed. These two reasons make websites very difficult for laypeople, especially teachers in educational institutions. Teachers have simple duties and functions in teaching. Technically, a teacher must be able to operate applications, both websites and social media information media. On the other hand, a teacher also needs a media for publishing information related to the profession being pursued, not only the publication of personal information, daily activities, but also the publication of teaching materials, new things related to learning, both to students and to the general public. The problem that arises is that not all teachers can create reliable websites and online access. Based on the survey results, at LPD Al Bahjah there are teachers who are very enthusiastic about operating personal websites. The solution offered is in the form of website development on a platform that has a template that is integrated with artificial intelligence in the process of personifying the user interface and selecting a website theme according to user input. The results of the community service carried out are that the community service participants are very enthusiastic in socializing website development, not only general technical use but also successfully creating personal websites.